The Antidepressant Mirtazapine Activates Hepatic Macrophages, Facilitating Pathogen Clearance While Limiting Tissue Damage in Mice - Davis, Rachelle Paige; Almishri, Wagdi; Jenne, Craig Neal; Swain, Mark Gordon (Frontiers in Immunology, 2020)
Background and Aims Mirtazapine is an atypical antidepressant with antagonist activity for serotonin and histamine receptors. Clinical and experimental evidence suggests that, in addition to treating depression, mirtazapine also alters liver innate immunity and suppresses immune-driven hepatic macrophage activation. Liver macrophages, Kupffer cells, represent the largest collection of fixed macrophages in the body and are critical in regulating hepatic immunity. In addition to their capacity to regulate inflammation, Kupffer cells are key sentinels for clearing blood-borne pathogens, preventing their dissemination within the body. This process involves pathogen capture, phagocytosis, and activation-induced killing via reactive oxygen species (ROS) production. Therefore, we speculated that mirtazapine might adversely alter Kupffer cell pathogen-associated activation and killing. Methods Mice were treated with mirtazapine and time-dependent changes in Kupffer cells were characterized using intravital microscopy. Macrophage and neutrophil responses, bacterial dissemination, and liver damage were assessed following i.v. infection with a pathogenic strain of S. aureus. Results Mirtazapine rapidly (within 1.5 h) activates Kupffer cells, indicated by a loss of elongated shape with cellular rounding. However, this shape change did not result in impaired pathogen capture function, and, in fact, generated enhanced ROS production in response to S. aureus-induced sepsis. Neutrophil dynamics were altered with reduced cellular recruitment to the liver following infection. Bacterial dissemination post-intravenous administration was not altered by mirtazapine treatment; however, hepatic abscess formation was significantly reduced. Conclusions Mirtazapine rapidly activates Kupffer cells, associated with preserved bacterial capture functions and enhanced ROS generation capacity. Moreover, these changes in Kupffer cells were linked to a beneficial reduction in hepatic abscess size. In contrast to our initial speculation, mirtazapine may have beneficial effects in sepsis and warrants further exploration.